Faktor Psikologi dalam Self-Regulated Learning dan Pengaruhnya terhadap Kemampuan Akademik Mahasiswa dalam Mata Kuliah Statistik Pendidikan - Elviana Elviana; Susanti Susanti; Raudhatul Munawwarah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Educational Statistics plays a central role in equipping university students with analytical skills and data-based decision-making, yet many students still struggle to learn this course effectively. This study aims to analyze psychological factors within self-regulated learning (SRL) and their influence on students’ academic performance in an Educational Statistics course. A quantitative approach with an ex post facto design was employed. Participants were 66 fourth-semester students from three Islamic State Higher Education Institutions (PTKIN) in Aceh, selected using purposive sampling. SRL was measured using a Likert-scale questionnaire assessing motivation, self-efficacy, metacognition, self-control, emotions, learning goals, and environmental structuring, while academic performance in Educational Statistics was measured using an essay test on basic statistical concepts. Data were analyzed using descriptive statistics, normality and linearity tests, and Spearman correlation. The results indicated that students’ SRL was at a moderate level, with self-efficacy and self-control emerging as the strongest components, whereas environmental structuring was the weakest. The correlation between SRL and Statistics achievement was positive but weak and non-significant (râ‚› = 0.213; p = 0.087), accounting for approximately five percent of the variance in scores. These findings suggest that SRL functions more as a supporting factor alongside other determinants such as prior mathematical ability, teaching quality, and statistics anxiety. Practically, SRL development in Educational Statistics courses should emphasize explicit training in concrete strategies (study planning, time management, environmental regulation, and help-seeking) integrated with emotional regulation to enhance students’ academic performance and learning readiness.